Unlocking cultural riches: navigating cultural terms translation in ‘The Treasure’ Egyptian movie - Noureldin Mohamed Noureldin Abdelaal (Cogent Arts & Humanities)
This research Investigates the translation strategies of subtitling culture-terms in (The Treasure)’s Egyptian movie. The study places particular emphasis on a spectrum of cultural references encompassing personal names, geographical locations, culinary items, and more. Employing a qualitative methodology, this inquiry investigates the intricate set of strategies utilized in the subtitling of cultural references, adopting the theoretical framework presented by Pedersen. Through the application of Pedersen’s framework and a thorough examination of subtitling strategies in ‘The Treasure,’ this study highlights the prevalence of certain strategies, notably omission, and casts light on the intricate interplay of language, culture, and translation in the realm of subtitling. In essence, this research contributes to an enriched comprehension of how subtitlers navigate the intricate terrain of translating cultural references in audiovisual content.